Single stage buck-boost DC-AC neutral point clamped inverter - Andrew, A. (2013)
This paper proposes a new single stage buck-boost DC-AC neutral point clamped inverter topology which integrates the cascaded configurations of recently introduced inductor-capacitor-capacitor-transformer impedance source network (by Adamowicz) and classic NPC configuration. As a consequence, it has enhanced buck-boost functionality and low output voltage distortions compared to the traditional Z-source inverter; it has continuous input current which reduces the source stress and inverter noise; it also contains two built-in capacitors which can block the DC current in the transformer windings thus preventing the core from saturation; lowers the voltage stresses and power losses of inverter switches and reduces the sizes of filtering devices and as well as obtains better output performance compared to the original two-level Z-source inverters. A phase disposition pulse width modulation technique with minimum switching counts is implemented for the proposed topology. Simulation results as well as experimental results are presented to verify the behaviors of proposed configuration.